2021
DOI: 10.1136/jitc-2020-001872
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and the immune system: taking steps to improve responses to cancer immunotherapy

Abstract: The remarkable success of cancer immunotherapies has provided new hope to cancer patients. Unfortunately, a significant proportion of patients remain unable to respond to immunotherapy or maintain durable clinical responses. The lack of objective responses likely results from profound immune dysfunction often observed in patients with cancer. There is substantial evidence that exercise and physical activity can reduce incidence and improve outcomes in cancer patients. As the immune system is highly responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 145 publications
5
66
0
Order By: Relevance
“…There is a growing body of evidence investigating the mechanisms by which exercise modulates immunity. Much of this research points to effects on natural killer (NK) and T cells, rather than to components of humoral immune responses [ 7 ]. These are also the immune cells that are targeted by ICIs, indicating that the anti-tumor effects of both exercise and checkpoint blockade may be synergistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence investigating the mechanisms by which exercise modulates immunity. Much of this research points to effects on natural killer (NK) and T cells, rather than to components of humoral immune responses [ 7 ]. These are also the immune cells that are targeted by ICIs, indicating that the anti-tumor effects of both exercise and checkpoint blockade may be synergistic.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been previously shown to be effective in the milieu of chemotherapy for decreasing the severity of chemotherapy- and cancer-related side effects [ 3 , 4 , 5 ]. Similarly, physical activity has been shown to reduce CRF and modulate the immune system through multiple mechanisms in cancer patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise can modulate the circulation of immune cells by a mechanism mediated by adrenergic signaling and blood flow-induced shear stress, facilitating immune surveillance by eradicating identified malignant cells [ 179 ]. Indeed, an increasing number of studies have found exercise-induced immune cell mobilization as a common phenomenon independent of age, gender, or tumor type [ 180 , 181 ].…”
Section: The Interplay Between Activity–rest Cycles and Cancermentioning
confidence: 99%
“…Chronically, physical activity promotes executive function, increases neurogenesis of the hippocampus and reduces inflammation as well as promotes healthy function of many of the organ systems of allostatic responses. Together, the effects of physical activity can be expected to reduce acute activation, promote habituation to future stressors and counteract adverse effects of allostatic load on target organ systems [ 145 , 146 ].…”
Section: Considerations For Interventionsmentioning
confidence: 99%